Cooperative condensation of RNA-DIRECTED DNA METHYLATION 16 splicing isoforms enhances heat tolerance in Arabidopsis - Jing Ma; Shuai Li; Tengyue Wang; Zhen Tao; Shijie Huang; Ning Lin; Yibing Zhao; Chuanhong Wang; Peijin Li (Nature Communications)
Abstract Dissecting the mechanisms underlying heat tolerance is important for understanding how plants acclimate to heat stress. Here, we identify a heat-responsive gene in Arabidopsis thaliana, RNA-DIRECTED DNA METHYLATION 16 (RDM16), which encodes a pre-mRNA splicing factor. Knockout mutants of RDM16 are hypersensitive to heat stress, which is associated with impaired splicing of the mRNAs of 18 out of 20 HEAT SHOCK TRANSCRIPTION FACTOR (HSF) genes. RDM16 forms condensates upon exposure to heat. The arginine residues in intrinsically disordered region 1 (IDR1) of RDM16 are responsible for RDM16 condensation and its function in heat stress tolerance. Notably, RDM16 produces two alternatively spliced transcripts designated RDM16-LONG (RDL) and RDM16-SHORT (RDS). RDS also forms condensates and can promote RDL condensation to improve heat tolerance. Our findings provide insight into the cooperative condensation of the two RDM16 isoforms encoded by RDM16 splice variants in enhancing heat tolerance in Arabidopsis.